ANALISIS KEBIJAKAN PEMERINTAH TERKAIT ANCAMAN PENGANGGURAN PASCA KENAIKAN INFLASI YANG TERJADI DI KOTA BATAM - Sartika Rahmawati; Billy Tan; Dewi Sunarwati; Muhammad Farhan; Lina Lina (UNIVERSITAS MARITIM AMNI SEMARANG, 2022)
Inflation and unemployment are the absence of quality economic development which are persistent and difficult challenges for the State of Indonesia. Judging from the absence of the Phillips curve in Indonesia, there is no correlation between inflation and unemployment. The trend of the Phillips curve stems from the correlation between unemployment and economic expansion. It depends on the state of the economy to determine which unemployment and inflation to tackle first. Reducing unemployment should be a national priority, which requires macro and micro policies.